Edukasi dengan Pendekatan Self-Directed Learning untuk Meningkatkan Pengetahuan dan Keterampilan Diabetesi dalam Pencegahan Ulkus Diabetikum - Ainul Yaqin Salam; Ana Fitria Nusantara (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus (DM) can cause serious complications, including impaired peripheral tissue perfusion that risks diabetic ulcers and amputation. The Self-Directed Learning (SDL) approach is an effective self-education strategy in improving the understanding and skills of DM patients in preventing these complications. This community service program aims to improve the understanding and skills of lower extremity care in DM patients through education and hands-on training. Activities include counseling, foot self-examination, and proper foot care practices. Evaluation results showed significant improvement in participants' understanding of diabetic ulcer prevention, awareness in maintaining blood sugar levels, and selection of appropriate footwear. In addition, skills in foot self-examination, proper nail trimming, and moisturizer application also improved. The SDL approach proved effective in increasing participants' engagement in the learning process, so they were more motivated to apply the knowledge gained in their daily lives. This program indicates that SDL-based education can be an effective strategy in improving the foot health of people with DM and preventing serious complications.